An integrated approach for optimising coal purchase and supply logistics network. (2016) - Jiang, Xiushan; Fu, Jiahui; Yuan, Aqian; Song, Liying
The location problem of coal logistics centre is a critical issue raised when optimising the coal logistics network to reduce logistics cost. Furthermore, the choice of coal suppliers is vital to ensure the quality of coal and to improve service levels. This paper proposes an integrated approach for optimising coal purchase and supply logistics network. A major advantage of the proposed approach is the integrated solution to location problem of coal logistics centre and supplier selection problem, which can simultaneously optimise the entire coal logistics network. This inventive methodology has three main components. First, it develops a coal supply logistics network optimisation model. Second, it builds coal purchase logistics network optimisation model. Third, it uses genetic algorithm (GA) to simultaneously solve the coal supply logistics network optimisation model and coal purchase logistics network optimisation model. For demonstration purposes, the paper carries out a real case study.